Deciphering the Spectral Tuning Mechanism in Proteorhodopsin: The Dominant Role of Electrostatics Instead of Chromophore Geometry. Issue 28 (5th April 2022) - Church, Jonathan R.; Amoyal, Gil S.; Borin, Veniamin A.; Adam, Suliman; Olsen, Jógvan Magnus Haugaard; Schapiro, Igor
Abstract: Proteorhodopsin (PR) is a photoactive proton pump found in marine bacteria. There are two phenotypes of PR exhibiting an environmental adaptation to the ocean's depth which tunes their maximum absorption: blue‐absorbing proteorhodopsin (BPR) and green‐absorbing proteorhodopsin (GPR). This blue/green color‐shift is controlled by a glutamine to leucine substitution at position 105 which accounts for a 20 nm shift. Typically, spectral tuning in rhodopsins is rationalized by the external point charge model but the Q105L mutation is charge neutral. To study this tuning mechanism, we employed the hybrid QM/MM method with sampling from molecular dynamics. Our results reveal that the positive partial charge of glutamine near the C14 −C15 bond of retinal shortens the effective conjugation length of the chromophore compared to the leucine residue. The derived mechanism can be applied to explain the color regulation in other retinal proteins and can serve as a guideline for rational design of spectral shifts. Abstract : There are two phenotypes of proteorhodopsin exhibiting an environmental adaption to the ocean's depth. These are blue‐absorbing proteorhodopsin (BPR) and green‐absorbing proteorhodopsin (GPR). The key to the blue/green shift between these variants originates from position 105, where BPR contains a glutamine (Q) and GPR a leucine (L). In this work it was found that Q105 is responsible for generating a positive electrostatic potential near the retinal chromophore leading to the observed blue‐shift in BPR.